Creating Competitive Advantages for Companies by Developing Strategic Human Resource Management in the Face of the Challenges of the Revolution 4.0 - Kosasih (International Journal of Science and Society, 2019)
Since the development of technology with the Internet of Thing and Artificial Intelligence or what we know as the 4.0 industrial revolution, the competition for each company is to survive and develop very fast. For this reason, every organization or company must be able to show a competitive advantage that distinguishes the company from others. One of the efforts to create this competitive advantage is to increase the human resources the company has. For this effort, the organization or company must be able to develop strategic human resource management. Therefore, the aim of this research is to describe the influence of the concept of corporate strategic human resource management that can affect competitive advantage. The method used is library research by processing literature related to this study using a qualitative approach. The research results obtained from the literature used show that both strategic human resource management is very influential for the company's competitive advantage. The implication of this research is expected to contribute in determining business strategy and policy through the theories of this research.